Flouting Maxim in SpongeBob Movie: Sponge on the Run - Ramadhanisya Ramadhanisya; Sri Hartati (JEdu: Journal of English Education, 2021)
Maxims are rules for determining whether the speaker is being cooperative in a conversation or not. When a speaker refuses to be cooperative during a conversation, this is known as flouting of maxim. This research focuses on flouting maxims uttered by the characters in The SpongeBob Movie: Sponge on the Run. The objective of this research is to identify the types of flouting maxims contained in this movie. The researcher used the descriptive qualitative method to analyze the data. The result of this research showed that the researcher found 41 utterances that flout the maxim in The SpongeBob Movie: Sponge on the Run. There are flouting the maxim of quality (6 data), flouting the maxim of quantity (16 data), flouting the maxim of relevance (15 data), and flouting the maxim of manner (9 data). The number of utterances and the number of flouting maxims used are different because one utterance may include more than one flouting maxim.